2014
DOI: 10.1021/jp5014913
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Intrastrand Adducts Sensitize DNA to Base Damage by Hydrated Electrons

Abstract: The oligonucleotide TTTTTGTGTTT with or without a cisplatin adduct was reacted with hydrated electrons generated by ionizing radiation. Hydroxyl radicals were quenched with ethylenediaminetetraacetic acid (EDTA), and the solutions were bubbled with wet nitrogen to eliminate oxygen, a scavenger of hydrated electrons. Prior to irradiation, the structure of the initial cisplatin adduct was identified by mass spectrometry as G-cisplatin-G. Radiation damage to DNA bases was quantified by high-performance liquid chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Nevertheless, when the irradiated oligonucleotide was digested to deoxyribonucleosides followed by HPLC analysis, the detachment of cisPt by e − aq was observed. These results are consistent with the previous observation by HPLC and gel sequencing analysis of radiolysis products from longer 11-mer oligonucleotides; 20,22 as well the observation of the strong enhancement of single and double strand break formation due to e − aq in γ-irradiated plasmid DNA-cisplatin complexes. 19 Taken together, these results strongly suggest that, in cells, the radiosensitization of DNA by cisplatin adducts probably results, at least in part, from the increase in the rate constant of the reaction of e − aq with DNA and formation Pt I .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Nevertheless, when the irradiated oligonucleotide was digested to deoxyribonucleosides followed by HPLC analysis, the detachment of cisPt by e − aq was observed. These results are consistent with the previous observation by HPLC and gel sequencing analysis of radiolysis products from longer 11-mer oligonucleotides; 20,22 as well the observation of the strong enhancement of single and double strand break formation due to e − aq in γ-irradiated plasmid DNA-cisplatin complexes. 19 Taken together, these results strongly suggest that, in cells, the radiosensitization of DNA by cisplatin adducts probably results, at least in part, from the increase in the rate constant of the reaction of e − aq with DNA and formation Pt I .…”
Section: Resultssupporting
confidence: 93%
“…19 Moreover, capture of e − aq by the base also creates base damage, such as 5,6-dihydrothymine, which is much more important in DNA-cisPt complexes than in DNA without cisPt. 22 …”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that hydrated electrons induce damage to thymines as well as detachment of the cisplatin moiety from both guanines in the oligonucleotide. The amount of free cisplatin (i.e., the cleavage of two Pt-G bonds) was found to be much larger than that of the products resulting from the cleavage of a single bond [181,182]. The errors represent the deviation of three identical measurements. )…”
Section: Transient Anions In Dna Bound To Platinum Chemotherapeutic Amentioning
confidence: 92%
“…This type of radiosensitization was investigated in more detail by irradiating with a γ source the oligonucleotide TTTTTGTTGTTT with or without cisplatin bound to the guanines [181]. Using scavengers and by eliminating oxygen, the oligonucleotide was shown to react with hydrated electrons.…”
Section: Transient Anions In Dna Bound To Platinum Chemotherapeutic Amentioning
confidence: 99%
“…Such a resonance in solution would have much lower energy owing to polarization of the molecular orbitals of electrons and vibrational and phonon modes of surrounding water molecules (i.e., polaron formation); binding of cisplatin to DNA could also lower the resonance energy. Thus, according to the results of Behmand et al, 44,45 the formation of TNI at the site of cisplatin could considerably increase the formation of radicals owing to detachment of the Pt drug and damage to the bases. Assuming that the core-excited resonances at 4.6, 9.6, and 13.6 eV have a behavior similar to the lowest energy TNI in cisplatin-DNA complexes, these higher energy anion states could also strongly amplify the formation of radicals from DNA, in the presence of cisplatin.…”
Section: B Increasing Ssb and CL Yields With Cisplatinmentioning
confidence: 96%